Transfixiánt wound of the heart: Exceptional etiology and topography - Armand Ugon, César; Otazu Correa, Heber; Burastero, Mercedes (Cirugía del Uruguay, 1984)
The unusual topographic-etiological character of the detectable cause of this heart injury instance is pointed out. No similar cases having been found in local or foreign medica! literatura. Quite differently from a'· bullet shot, cutting wounds -"or by pricking objects"- only occasionally may endanger the heart integrity when acute hemodynamic failure due to interna! hemorrhage it must be remembered that apart from highly probable lesion of great vessels, the cardiac valvas, alone o associated, may be affected by a wound in